Novel health systems service design checklist to improve healthcare access for marginalised, underserved communities in Europe. Issue 4 (6th April 2020) - Lazarus, Jeffrey V; Baker, Lee; Cascio, Mario; Onyango, Denis; Schatz, Eberhard; Smith, Alyna C; Spinnewijn, Freek
Abstract : Background: Marginalised communities such as homeless people, people who use drugs (PWUD), lesbian, gay, bisexual, transgender and intersex people (LGBTI), prisoners, sex workers and undocumented migrants are at high risk of poor health and yet face substantial barriers in accessing health and support services. The Nobody Left Outside (NLO) Service Design Checklist aims to promote a collaborative, evidence-based approach to service design and monitoring based on equity, non-discrimination and community engagement. Methods: The Checklist was a collaborative project involving nine community advocacy organisations, with a focus on homeless people, PWUD, LGBTI people, prisoners, sex workers, and undocumented migrants. The Checklist was devised via a literature review; two NLO platform meetings; a multistakeholder policy workshop and an associated published concept paper; two conference presentations; and stakeholder consultation via a European Commission-led Thematic Network (including webinar). Results: The NLO Checklist has six sections in line with the WHO Health Systems Framework. These are: (1) service delivery, comprising design stage (6 items), services provided (2 items), accessibility and adaptation (16 items), peer support (2 items); (2) health workforce (12 items); (3) health information systems (7 items); (4) medical products and technologies (1 item); (5) financing (3 items); and (6) leadership and governance (7 items). It promotes the implementation of integrated (colocated or linked) healthcare services that are community based and people centred. These should provide a continuum of needs-based health promotion, disease prevention, diagnosis, treatment and management, together with housing, legal and social support services, in alignment with the goals of universal health coverage and the WHO frameworks on integrated, people-centred healthcare. Conclusions: The Checklist is offered as a practical tool to help overcome inequalities in access to health and support services. Policymakers, public health bodies, healthcare authorities, practitioner bodies, peer support workers and non-governmental organisations can use it when developing, updating or monitoring services for target groups. It may also assist civil society in wider advocacy efforts to improve access for underserved communities.